MEMBATINKAN KARAKTER ANTI KORUPSI MELALUI INTEGRASI KURIKULUM - Anam (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2014)
Anti-corruption education at education institutions is a inheritance process of culture that should be conducted by conscious effort and planned manner to create an atmosphere of learning and active and characterlize learning process, so the students having personality and attitude that strong to resist various forms of corruption. As for its application in a class were performed by integration of value and education teaching anti-corruption into subjects course who was exist in college, namely a course called anti-corruption education. While outside of class, integration of value and education teaching anti-corruption could be done outside of class as in extracurricular and when school tuition in the community or at home. The process of education in substance wanted to exist in out put students preventing himself to not committed acts of corruption, prevent others to not committed acts of corruption by providing warning the person, and capable of detecting the presence of corruption.